Estudio de la participación de la secretaria ejecutiva como aporte al modelo de gestión pública empresarial del colegio mixto particular universidad península de Santa Elena, cantón la Libertad, AÑO 2015 - González Limones, Grelia Fabiola (2015)
Santa Elena's School Mixed Particular University Peninsula is committed to offer education to youths that enter with the Guarantee of the Address Districtal 24D02 according to the zonification, fulfilling what prepares the Regulation of Education. In such a sense the present investigation work has as main objective: To determine the Executive Secretary's participation in the Managerial Public Administration in Santa Elena's School Mixed Particular University Peninsula. The results of the investigation report that the secretaries of Santa Elena's School Mixed Particular University Peninsula have not concluded their studies of superior level and they maintain a participation limited in the process of managerial public administration of the institution, for what is suggested to welcome the proposal in which specific and interconnected strategies in a logical way are included in order to promote their insert in the administration process, leadership and taking of decisions that contribute to the development and improvement of the institutional image. KEYWORDS.Participation, Secretary, Management Public.